Evaluation of the accuracy of T-scan system and Cerec Omnicam system used in occlusal contact assessment - Rongkai Cao; Hui Xu; Jing Lin; Weicai Liu (Heliyon, 2023)
Purpose: The objective of the present study was to determine the accuracy of T-scan system and Cerec Omnicam system with respect to the evaluation of occlusal contact by quantitatively comparing the occlusal contact areas and the overlapping ratios of occlusal contact areas obtained from these systems. Material and methods: The occlusal contact of 20 adolescents with normal occlusion was measured with the T-scan system and the Cerec Omnicam system, respectively. The occlusal contact areas in the intercuspal position were then quantified with Adobe Photoshop CS6 Software. The same procedure was repeated for each subject using with 8 μm articulating paper as the control group. The overlapping ratio of T-scan system and Cerec Omnicam system was calculated respectively, which is defined as the ratio of overlapping areas comparing with those obtained from articulating paper. To examine the accuracy of T-scan system and Cerec Omnicam system, the Paired t-test was applied. The reproducibility of T-scan system was evaluated with Wilcoxon matched-pairs signed-ranks test by comparing the occlusal contact areas between two repeated measurements. In all statistical analysis, the level of significance was set to α = 0.05. Results: Results demonstrated measured occlusal contact areas were significantly different between those obtained between T-scan system and Cerec Omnicam system (P < 0.05). The tooth position of two-dimensional virtual dental arch established by T-scan system based on the width of the central incisor was in disagreement with the actual tooth position. The overlapping ratios obtained from Cerec Omnicam system were higher than those obtained from the T-Scan system (P < 0.05). The sensitivity of T-Scan system in anterior teeth area decreased when sensors are used more than once (P < 0.05). Conclusions: In the intercuspal position, the accuracy of Cerec Omnicam system for occlusal contact assessment is higher than that of T-scan system. The T-scan system demonstrates good reproducibility in the premolar region and the molar region, but poor reproducibility in the anterior teeth region. Clinical implications: In the intercuspal position, Cerec Omnicam system is more accurate than T-scan system, which can quantitatively analyze occlusal relationship in terms of number, position, size and distribution of occlusal contact points. When evaluating occlusal contacts, the accuracy of T-scan system in anterior teeth region is significantly lower than that of premolar and molar regions.